Microbiological Test and Antioxidant Activity of Moringa Leaf Brownies Substituted with Tempeh Flour which is High in Protein for Anemic Pregnant Women - Nugroho, Arie; Sutrio, Sutrio; Sari, Adinda Juwita; Kusdalinah, Kusdalinah (Jurnal Kesehatan, 2023)
Brownies are food, a distraction loved by all class ages. Most study regarding the added brownies' and other material shows that the product experience organoleptic changes and does not increase mark nutrition, including antioxidants. This study test marks microbiology and activity of leaf brownies antioxidants moringa substituted flour tempeh. This is the advanced study year, the second which brownies are the most liked, and the control will be compared in a manner mark microbiology and activity antioxidants. The research method in this study is draft random complete (RAL) with five replications. Leaf moringa, added to making these brownies, is porridge leaf moringa obtained from fresh leaf moringa, as much as 10% of the total flour. Treatment consisted of different composition bases comprising brownies from flour wheat compared flour tempeh with substitution tempeh flour, which is 100:0 (A1) and 75:25(A3), the most preferred panelist from the previous study. Good brownies products it controls, and A3 have marked microbiology following SNI standards to consume them safely. Activity value antioxidants from A3 are taller compared to controls. Recommended brownies products using leaf moringa as additional toppings to minimize decline activity antioxidants because of the oven.